The Importance of The Ijoza System in The Process of Teaching and Education by Mahmud Zamakhshari - Rahim, Akhter Muhammad (State Islamic Institute of Madura, 2020)
This article is based in one of the scientific legacies by Mahmud Zamakhshari on the work on spiritual education and morality